Strengthening the Integration of Internal and External Quality Assurance Systems in Indonesian Higher Education: Toward a Sustainable Culture of Quality - Ariel N. Rengkuan; Lando E. Sumarauw; Hartini Ngadiorejo; Deitje A. Katuuk; Joulanda A.M. Rawis; Ruth Umbase (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to analyze the structure, implementation, and interrelation between the Internal Quality Assurance System (IQAS) and the External Quality Assurance System (EQAS) in Indonesian higher education institutions. These systems, mandated by Law No. 12 of 2012, are fundamental to ensuring continuous improvement, accountability, and competitiveness in national higher education. This paper aims to provide a comprehensive understanding of both systems, their regulatory foundations, operational mechanisms, and challenges in implementation, as well as to propose strategic recommendations for enhancing their synergy. Materials and methods. This study applied a systematic literature review approach by collecting and analyzing national regulations, institutional policy documents, and recent scholarly publications related to higher education quality assurance. The review process involved identifying, classifying, and synthesizing literature based on key themes such as quality concepts, legal frameworks, operational mechanisms, and institutional practices. Data were analyzed thematically to reveal patterns, gaps, and best practices in the execution of IQAS and EQAS across Indonesian universities. Results. The findings indicate that IQAS functions as an autonomous internal mechanism designed to ensure continuous quality improvement through the PPEPP cycle (Setting, Implementation, Evaluation, Control, and Improvement). EQAS, on the other hand, serves as an external validation process conducted by accrediting bodies such as BAN-PT and LAM. Despite their complementary roles, both systems face challenges including leadership commitment, limited resources, administrative formalism, and fragmented integration. A synergistic relationship between IQAS and EQAS fosters a sustainable quality culture and institutional excellence. Conclusions. The study concludes that the effectiveness of quality assurance in Indonesian higher education depends on institutional commitment, human resource competence, and the harmonization of internal and external mechanisms. Strengthening digital-based quality information systems, risk-based management, and inter-institutional collaboration is essential to building a culture of continuous quality improvement and achieving global competitiveness.